Polyvinyl Alcohol Hydrogel Irradiated and Acetalized for Osteochondral Defect Repair: Mechanical, Chemical, and Histological Evaluation after Implantation in Rat Knees - N. A. Batista; A. A. Rodrigues; V. P. Bavaresco; J. R. L. Mariolani; W. D. Belangero (International Journal of Biomaterials)
Polyvinyl Alcohol (PVA) hydrogel plugs were implanted in artificial osteochondral defects on the trochlear groove of rat knees. After 0, 3, 6, 12, and 24 weeks of followup, samples containing the implants were mechanically evaluated by creep indentation test, chemically, and histologically by optical microscopy. The mechanical test pointed towards an increase of the implant creep modulus and the chemical analysis exhibited an increasing concentration of calcium and phosphorus within the implants over time. Optical microscopy showed no foreign body reaction and revealed formation, differentiation, and maintenance of new tissue at the defect/implant interface. The absence of implant wear indicated that the natural articular lubrication process was not disturbed by the implant. The performance of the irradiated and acetalized PVA was considered satisfactory for the proposed application.